2016
DOI: 10.3389/fphys.2016.00437
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hyperbilirubinemia Alters Neonatal Cardiorespiratory Control and Induces Inflammation in the Nucleus Tractus Solitarius

Abstract: Hyperbilirubinemia (HB) occurs in 90% of preterm newborns. Moderate HB can induce acute neurological disorders while severe HB has been linked to a higher incidence of apneas of prematurity. The present study aimed to test the hypothesis that even moderate HB disrupts cardiorespiratory control in preterm lambs. Two groups of preterm lambs (born 14 days prior to term), namely control (n = 6) and HB (n = 5), were studied. At day 5 of life, moderate HB (150–250 μmol/L) was induced during 17 h in the HB group afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Results from a past study by our team showed that the presence of brainstem inflammation induced by a moderate hyperbilirubinemia blunted the cardiorespiratory inhibition normally observed during both laryngeal and pulmonary chemoreflexes (Specq et al, 2016). The absence of any effect in the present experiments in full-term lambs, despite a preliminary indication (see next paragraph) that brainstem inflammation was also present, is probably be linked to the fact that the former study was performed on preterm lambs.…”
Section: Absence Of Effect Of Lipopolysaccharide Injection On Cardiorcontrasting
confidence: 50%
“…Results from a past study by our team showed that the presence of brainstem inflammation induced by a moderate hyperbilirubinemia blunted the cardiorespiratory inhibition normally observed during both laryngeal and pulmonary chemoreflexes (Specq et al, 2016). The absence of any effect in the present experiments in full-term lambs, despite a preliminary indication (see next paragraph) that brainstem inflammation was also present, is probably be linked to the fact that the former study was performed on preterm lambs.…”
Section: Absence Of Effect Of Lipopolysaccharide Injection On Cardiorcontrasting
confidence: 50%
“…The current study complements a previous publication on the same lambs showing electroencephalographic signs of acute HB encephalopathy and alterations of several cardiorespiratory reflex responses, as well as inflammation at the level of the cardiorespiratory centers (Specq et al, 2016). The latter led us to hypothesize that HB can also alter HRV, RRV, and cardiorespiratory interrelations in preterm lambs.…”
Section: Introductionsupporting
confidence: 86%
“…At the cardiorespiratory level, several studies have linked HB to apnea of prematurity (Amin, 2004; DiFiore et al, 2004; Johnson et al, 2009; Amin et al, 2014), and apnea is considered a common clinical sign of acute bilirubin encephalopathy in preterm infants (Govaert et al, 2003; Gkoltsiou et al, 2008). In a recent study, we also showed a decrease in respiratory rate and an increase in apnea duration in preterm lambs with moderate clinically-relevant HB (150–250 μmol/L) (Specq et al, 2016).…”
Section: Introductionmentioning
confidence: 75%
“…They arrived at the end of the 3 rd week scoring loss of consciousness. The study of Specq et al (7) included five preterm lambs with hyperbilirubinemia (150-250 μmol/L) and six healthy preterm lambs. They reported a decrease in breathing rate and increased apnea frequency, and they detected that the inhibition of laryngeal and pulmonary chemoreflexes and bradycardia were more common in the preterm lambs with hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Two in vitro studies performed on the effects of UCH on the myocardial tissue show that UCH damages it, and an in vivo study determines myocardial functional disorder that can be compensated (5,6) . A number of studies determine that bilirubin levels increase the tone of parasympathetic nervous system and cause heart rate variability (7,8) . To the best of our knowledge, there have been no reports on the high-level UCH effects over the ventricular functions on humans in vivo.…”
Section: Introductionmentioning
confidence: 99%